2021
DOI: 10.1002/nbm.4607
|View full text |Cite
|
Sign up to set email alerts
|

Automated facial–vestibulocochlear nerve complex identification based on data‐driven tractography clustering

Abstract: Small size and intricate anatomical environment are the main difficulties facing tractography of the facial-vestibulocochlear nerve complex (FVN), and lead to challenges in fiber orientation distribution (FOD) modeling, fiber tracking, region-of-interest selection, and fiber filtering. Experts need rich experience in anatomy and tractography, as well as substantial labor costs, to identify the FVN.Thus, we present a pipeline to identify the FVN automatically, in what we believe is the first study of the automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Based on the experience of our previous work (Zeng et al, 2021), the OCN is present in multiple fiber clusters, and the integration of these fiber clusters can represent an anatomical subdivision of the complete OCN. We obtain the fixed atlas by subdividing multi‐subject registered brainstem fibers into 200 clusters (clusters are labeled as 1–200).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the experience of our previous work (Zeng et al, 2021), the OCN is present in multiple fiber clusters, and the integration of these fiber clusters can represent an anatomical subdivision of the complete OCN. We obtain the fixed atlas by subdividing multi‐subject registered brainstem fibers into 200 clusters (clusters are labeled as 1–200).…”
Section: Methodsmentioning
confidence: 99%
“…where N cp was the number of correct predictions and N p was the total number of patients. The percentage of misclassification of the method was reflected by the following equation: (10) where N ip was the number of incorrect predictions. The lower the MR indicator, the better, as this may lead the surgeon to incorrect surgical planning prior to surgery.…”
Section: Qualitative and Visual Analysismentioning
confidence: 99%
“…6 Numerous studies have shown that preoperative identification of the FN can improve the rate of nerve preservation and predict postoperative deficits. [7][8][9] Diffusion MRI tractography is a potential tool for preoperatively predicting the path of the FN displaced by VS. 7,[10][11][12][13] Deterministic fiber tracking 11,14 and probabilistic fiber tracking 15,16 are the most common methods of identifying FN. The fiber propagation direction of the deterministic fiber tracking method is uniquely determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation